"California Mastitis" and "Modified Whiteside" tests as screening to caprine mastitis - dos Santos, Lúcia de Fátima L.; Castro, Roberto Soares; Costa, Elizabeth Oliveira da (Pesquisa Agropecuaria Brasileira, 1995)
The interpretation of screening tests is a major problem observed during the caprine mastitis control programmes. In this paper the California Mastitis Test (CMT) and a modified Whiteside (WM) test were studied as screening test to detect subclinical infection of udder in 126 milk samples collected from dairy goats (Saanen, Alpine, Toggenburg and Crossbred). The CMT <span style="line-height: 115%; font-family: ";Calibri";,";sans-serif";; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: PT-BR; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">≥ 2 and WM <span style="line-height: 115%; font-family: ";Calibri";,";sans-serif";; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: PT-BR; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">≥ 2 scores were admitted as the ideal screening level. The CMT showed the highest sensibility and specificity, being the recommended according to Youden index. When the tests were studied as a serial or paralell association, no significant advantage was observed.